Cone beam computed tomography (CBCT) in periodontal diseases: a Systematic review based on the efficacy model - Hassan Assiri; Ali Azhar Dawasaz; Ahmad Alahmari; Zuhair Asiri (BMC, 2020)
Abstract Background Periodontal diseases are prevalent among adult populations. Its diagnosis depends mainly on clinical findings supported by radiographic examinations. In previous decades, cone beam computed tomography has been introduced to the dental field. The aim of this study was to address the diagnostic efficacy of cone-beam computed tomographic (CBCT) imaging in periodontics based on a systematic search and analysis of the literature using the hierarchical efficacy model. Methods A systematic search of electronic databases such as PubMed, Scopus, Web of Science, and Cochrane was conducted in February 2019 to identify studies addressing the efficacy of CBCT imaging in Periodontics. The identified studies were subjected to pre-identified inclusion criteria followed by an analysis using a hierarchical model of efficacy (model) designed for an appraisal of the literature on diagnostic imaging modality. Four examiners performed the eligibility and quality assessment of relevant studies and consensus was reached in cases where disagreement occurred. Results The search resulted in 64 studies. Of these, 34 publications were allocated to the relevant level of efficacy and quality assessments wherever applicable. The overall diagnostic accuracy of the included studies showed a low or moderate risk of bias and applicability concerns in the use of CBCT. In addition, CBCT is accurate in identifying periodontal defects when compared to other modalities. The studies on the level of patient outcomes agreed that CBCT is a reliable tool for the assessment of outcomes after the treatment of periodontal defects. Conclusion CBCT was found to be beneficial and accurate in cases of infra-bony defects and furcation involvements.